Study of Potassium Hydrogen Tartrate Unseeded Batch Crystallization for Tracking Optimum Cooling Mode - Kherici, Samira; Benouali, Djillali; Benyetou, Mohamed; Ghidossi, Remy; Lacampagne, Soizic; Mietton-Peuchot, Martine (Oriental journal of chemistry, 2015)
The crystallization of organic compounds from solutions is responsible for the majority of organic solid materials produced by the chemical industry. A great deal of research carried out up to now, focused on batch crystallization modeling, simulation, optimization and control. This work aims to obtain the optimal cooling temperature strategy of a batch crystallizer made in our laboratory. Experiments were achieved to find out under our crystallizer constraints the maximum of the total volume of cream tartar crystals and the best crystal size distribution from aqueous solution without seeding. In our present study, the potassium hydrogen tartrate (cream of tartar) subject of our study is recovered from wine tartar, a solid byproduct of wine making using several successive cooling crystallization operations with water as solvent. For the firsts crystallizations we principally interested by the maximization of the yield and the optimization of time and energy. We compared the results of some cooling strategy; optimum cooling mode corresponds to the case in which final temperature of the crystallizer is reached at much faster rate as compared to other cooling modes. The final temperature of 12 °C is reached within 30 minutes. This optimum mod shows a typical cooling curve found in industrial practice derived from a constant refrigeration of the cooling bath. The potassium bitaratrate particle size distribution was characterized by Malvern laser particle size analyzer. The crystal yield increased as the final crystallizer temperature decreased, however, only small differences in terms of crystal properties were observed.